KONTRIBUSI SEKTOR KEHUTANAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KUANTAN SINGINGI - Windu Adi Prasetyo; Evi Sri Budiani; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The total area of Kuantan Singingi Regency reach ± 7656.03 km2. Forest area has reached 317 615 ha or 41.5% of the area of Kuantan SingingiRegency.District Own Source Revenue  (PAD) is the income was earned from all of sources income in the area and by managed the local government that includes local tax revenues, results of retribution, wealth management outcomes was separated areas and other legitimate local revenues.The purpose of this study was to find of the contribution value forestry sector to District Own Source Revenue  (PAD). The results showed that the contribution of the forestry sectorto district own source revenue(PAD) in Kuantan Singingi Regency in 2008, 2009, 2010 and 2011 is under 1% with a distribution in 2008 has the amount  of  0,45% (Rp 115.000.000 from Rp 25.380.245.966), the year 2009 amounted to 0,5% (Rp 115.000.00 from Rp 23.147.073.224), the year 2010 amounted to 0,53% (Rp 115.000.000 from Rp 21.435.798.449), and in 2011 amounted to 0,48% (Rp 115.000.000 from Rp 23.755.740.032), indeed in 2012 the contribution forestry sector is 0% from Rp 30.269.207.812.Keywords:Contribution, District Own SourceRevenue(PAD,)Forestry Sector